Constructing and managing patient death : a narrative inquiry : a thesis presented in partial fulfilment for the requirement for the degree of Masters of Science in Psychology (endorsed in Health Psychology) at Massey University, Albany, Auckland, New Zealand - Steyn, Wilmie-Minette (Massey University, 2015)
This research inquiry has sought to explore how medical consultants construct and manage patient death. Previous research in this area has focused on the influence of patient death on nurses and medical students or on family members. However no research could be found that specifically investigated what the influence of patient death was on medical consultants nor on how medical consultants constructed and managed patient death. This thesis aims to break new ground by examining this topic. Twelve consultants across six different specialities: Emergency medicine, Anaesthetics, Intensive care, General surgery, Internal medicine and Paediatrics; volunteered to be interviewed for this research project. Interviews were recorded, transcribed and then analysed using narrative inquiry in order to gain insights into the influence of patient death on consultants and also how they understand and manage patient death. Findings are discussed in two parts. The first part focuses specifically on the values that consultants hold and how these values underpin their particular identity as consultants. The research shows that consultants value being responsible, having support from others, being rational decision-makers, being good communicators, however they also value keeping their emotions compartmentalised until they felt it appropriate to display them. Consultants used these values to build the identity of a good doctor as one who is ethical and compassionate. Furthermore, consultants used these values to help them project the protagonist position they held within their narratives. The second part explores how consultants construct and manage patient death; both in a broad sense and with reference to specific cases. These findings indicated that consultants consider death not only as a relentless force without discriminatory power, but also as a natural process. Viewing death in these ways allowed consultants to construct death in two ways, depending on whether the death was due to an acute or chronic condition. For patients who died in acute circumstances, the consultants constructed death as a lost battle. For patients who died following long term illness, death was constructed as a merciful end. The case examples emphasized that these two distinct constructions of death allow consultants to manage patient death. They were able to resolve their own internal conflicts of feeling that they should be able to save all patients versus the reality that it is not possible to save everyone. This research contributes to the limited research in this area and fills a gap in the literature by specifically looking at consultants, a group that has not previously been considered.
Keywords: Hospital patients; Mortality; Death; Psychological aspects; Terminal care; Medicine; Specialities and specialists